(untitled) (Numerus academy review, 2026)
This study aims to identify bank insurance as a mechanism followed by insurance companies to distribute their insurance products through banks, in addition to the most important agreements that link banks with insurance companies active in the Algerian market, highlighting the most important advantages that distinguish bank insurance as well as its reality in Algeria during the period from 2013 to 2017. have concluded that there is a positive relationship between bank insurance and the production of insurance companies, but the premiums obtained by bank insurance remain very small and at low rates that did not exceed 3.64% throughout the study period.